Reconstruction of the Proximal Aspect of the Radius After Desmoplastic Fibroma Resection: A Case Report. Issue 1 (January 2019) - Lans, Jonathan; Chebib, Ivan A.; Castelein, René M.; Chen, Neal C.; Lozano-Calderón, Santiago
Abstract : Case: Desmoplastic fibromas are tumors of fibrous tissue that rarely are diagnosed. We present the case of a 27-year-old man who presented with pain of the forearm that was initially diagnosed as a muscle strain. A computed tomography-guided core biopsy revealed a desmoplastic fibroma. Consequently, the patient was treated with a resection of the proximal aspect of the radius followed by reconstruction with use of a vascularized fibular autograft. Conclusion: At the 2-year follow-up, radiographs showed integration of the autograft; additionally, good results were noted with the Patient-Reported Outcomes Measurement Information System (PROMIS) Upper Extremity and Physical Function Short Form T-score and the QuickDASH (an abbreviated version of the Disabilities of the Arm, Shoulder and Hand Score [DASH]) questionnaire, along with good range of motion.